Financial inclusion also leads to social inclusion: Myth or reality? : evidences from self-help groups led microfinance of Assam - Shrabanti Maity (Journal of Innovation and Entrepreneurship, 2023)
Microfinance is globally trusted for corroborating the upliftment of the rural vulnerable poor sections. It is looked upon as a means of credit-based poverty alleviation through financial inclusion. India also witnesses the same. In India, the self-help group bank linkage programme (SHG-BLP) is architected by NABARD in 1992 as a pilot project. The programme was mainstreamed in 1996 to link unorganised with the formal financial sector. In Assam, microfinance services are made available through SHG-BLP registered under Deendayal Antyodaya Yojana-National Rural Livelihoods Mission. Central Assam is the epicentre of operative SHG-BLP. This backdrop motivates us to explore the contribution of SHG-BLP in financial and social inclusion of the marginalised rural people of central Assam. Two self-developed indices, viz., financial inclusion index and social exclusion index are constructed by applying Multiple Correspondence Analysis. The impact analysis is facilitated by the Propensity Score Matching method. The study concludes that the SHG-BLP is successful in ensuring financial inclusion and simultaneously also assists in reducing social exclusion among the stakeholders.
Keywords: 650; Propensity score matching; Central Assam; Financial inclusion index; Multiple correspondence analysis; Self-help group bank linkage programme; Social exclusion index